The emerging roles of GPR158 in the regulation of the endocrine system - Lin, Jinju; Li, Qin; Lei, Xiaohua; Zhao, Huashan (Frontiers in Cell and Developmental Biology, 2022)
G protein-coupled receptor 158 (GPR158) is a member of class C G protein-coupled receptors (GPCRs) and is highly expressed in the central nervous system (CNS) while lowly expressed in peripheral tissues. Previous studies have mainly focused on its functions in the CNS, such as regulating emotions, memory, and cognitive functions, whereas studies on its role in the non-nervous system are limited. It has been recently reported that GPR158 is directly involved in adrenal regulation, suggesting its role in peripheral tissues. Moreover, GPR158 is a stable dimer coupled to the regulator of G protein signaling protein 7 (RGS7) that forms the GPR158-RGS7-Gβ5 complex. Given that the RGS7-Gβ5 complex is implicated in endocrine functions, we speculate that GPR158 might be an active component of the endocrine system. Herein, we reviewed the relevant literature on GPR158, including its molecular structure, regulatory molecules, expression, and functions, and highlighted its roles in endocrine regulation. These findings not only enhance our understanding of GPR158 from an endocrine perspective but also provide valuable insights into drug exploration targeting GPR158 and their applicability in endocrine disorders.